Reuse of patients' own drugs in hospitals in Ghana; the evidence to support policy - Pauline Boachie-Ansah; Berko Panyin Anto; Afia Frimpomaa Asare Marfo (BMC, 2019)
Abstract Background Given the documented benefits of Patient Own Drugs (PODs) in most developed countries and scanty data on PODs management in developing countries the aim of the study was to evaluate the assessment, quality and extent of PODs use among hospitalised patients. Furthermore the perceived benefits and challenges in executing PODs management by the pharmacy staff in the hospital setting were explored. Method This was a cross-sectional descriptive study. Three hundred patients with chronic diseases admitted in a teaching hospital were purposively sampled. Quality assessment criteria was developed as part of the data collection tool for assessing the quality of PODs. Furthermore, two ward pharmacists and two in-charge nurses at the medical ward were purposively sampled for a face to face interview using an interview guide to find out the hospitals' medicines management system and policy for PODs. In addition, 130 pharmacy staff were interviewed using a structured questionnaire to find out how PODs were managed. Data was analysed with SPSS version 17. Results The study showed that 140 (46.6%) of patients brought their PODs on admission. Of these, only 38 (12.7%) were told to bring them whenever they were on admission. Of the 115 (38.3) patients whose PODs were documented as part of medication history, 28 (24.3%) of them had their PODs continued whilst on admission and 11(9.5%) of discharged prescription included PODs. In assessing the quality of PODs 61.6% of 845 PODs were suitable for reuse. Only 19.8% of pharmacy staff attested to the fact that all PODs identified were assessed. The common benefit of PODs cited by pharmacy staff was improving medication history taking whilst the major challenge was difficulty in determining the expiry dates of PODs without original packages. Conclusion About a half of patients with chronic diseases brought PODs with them on admission. The majority of PODs appeared to be suitable for use as presented but only a few were actually used for the patients. Most pharmacy staff were not involved in patients own drugs management at the hospital. There is the need for a policy to streamline PODs management in the teaching hospital.